Antiplasmodial Activity and Cytotoxicity of 10β-Aminoquinolinylethylethers of Artemisinin - N’Da, D. D.; Lombard, M. C.; Clark, J. A.; Connelly, M. C.; Matheny, A. L.; Sigal, M.; Guy, K. R. (Drug Research, 2013)
Each year roughly 800 000 people die of malaria, with 95% being African children. The shortcomings of the current drugs and the emergence of P. falciparum resistance to the artemisinin class of compounds warrant the search for new classes or derivatives. In search for such compounds, a series of 10β-aminoquinolinylethylethers of artemisinin, previously synthesized from this laboratory were screened for antimalarial activity against both the chloroquine-susceptible 3D7 and -resistant K1 strains of P. falciparum. Their cytotoxicity was also assessed against HEK 293 and HepG2 cell lines.The parasitic and mammalian cells were incubated with compounds at various concentrations for 72 h. The antimalarial activity was determined using SYBR Green I-based fluorescence. For cytotoxicity determination, cells were grown to confluence and CellTiter-Glo luminescent cell viability assay was used.All derivatives proved to be active against both strains with good selectivity towards the parasitic cells. The derivative 11 featuring 2 artemisinin moieties and an aminoethylpiperazine linker was the most active of all. It possessed 17- and 166-fold more potency than artemether against 3D7 (EC50: 9.5 vs. 166 nM) and K1 (10.9 vs. 1723.3 nM), respectively, while was found to be as potent as artesunate against both strains.Derivative 11 stands as a good candidate to be further investigated primarily in vitro in comparison with an equimolar combination of chloroquine (CQ) and artemisinin to ascertain its advantages, if any, over the combination.
Keywords: malaria; P. falciparum; selectivity